Attachment styles and psychosocial and emotional reactions to dating violence: mediating effects of active coping and self-criticism - Rehman, Sadaf; Saleem, Sadia; Zahra, Sayyeda Taskeen (Journal of the Pakistan Medical Association, 2025)
Objective: To examine the mediating effect of active coping and self-criticism in the relationship of attachment styles and psychosocial and emotional reactions in young adults with dating violence. Method: The cross-sectional study was conducted from January 1 to April 30, 2024, in Lahore, Pakistan, after approval from the ethics review committee of the Institute of Clinical Psychology, University of Management and Technology, Lahore. The sample was raised from among students of either gender aged 18-26 years studying at various public and private universities in Lahore. Data was collected using the Attachment Styles Scale, Dating Violence Scale, Self-Criticism Scale and the Psychosocial and Emotional Reactions Scale. Data was analysed using SPSS 25. Results: Of the 284 participants, 105(37.4%) were males and 179(62.6%) were females. The overall mean age was 22.35±2.01 years. A significant negative association was found among attachment styles (p<0.01), active coping (p<0.01), self-criticism (p<0.01) and psychosocial and emotional reactions (p<0.01). Furthermore, active coping and self-criticism fully mediated (p<0.001) in the association of attachment styles and psychosocial and emotional reactions in young adults with dating violence. Conclusion: Counsellors offering individualised treatment strategies and preventive measures may help their clients avoid major outcomes from their psychological and emotional responses to dating violence. Key Words: Attachment styles, Coping mechanism, Self-criticism, Psychosocial and emotional reactions, Dating violence, Young adults.